PENGARUH PENERAPAN LKPD BERBASIS PENDEKATAN SAVI (SOMATIC AUDITORY VISUAL INTELEGENCY) DALAM PEMBELAJARAN IPA TERPADU TIPE CONNECTED TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VIII SMPN 12 PADANG - Annisa Kurniawati; Djusmaini Djamas; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2016)
The lowness of students achievement in science competence is caused by several factors, such as the learning process which is still teacher-centered so that the students involvement in learning process is less and student worksheet which is used cannot motivate the students to learn. type connected approach on Integrated Science toward students achievement of IPA competence at class VIII SMPN 12 Padang. This experiment was quasi experiment. it used Randomizes Control Group Only Design. The population of the research is all student in grade VIII at the 2nd semester in SMPN 12 Padang in year of 2015/2016. The sampling technique of Purposive Sampling. Research sample was class VIII-4 as control class and VIII-7 as experimental class. Instruments used in this research were behavioral observation sheet to assess the behavior competency, written test to assess the knowledge and rubric to assess the skill competence. Data analysis technique used in this research was hypotheses test about the equality of two mean and, regression and correlation tests. The result of the analysis based on the research about the average score at the attitude competence, knowledge and skill from experiment group are 81,50; 76,49; and 79,48. On the other hand, the score from control group are 72,15; 59,48; and 74,28. From the two average test at attitude competence, it is obtained t observed = 2.68 and t table = 2.04; at knowledge competence, it is obtained t observed = 5,46 and t table = 2,04; and at skill competence,it is obtained t observed = 2,19 and t table = 2,00. At those three competences the scores obtained t observed > t table, which mean t observed are outside of Ho, therefore Hi are accepted. The level of student worksheet score toward the score of knowledge competence is medium and the effect of student worksheet is about 35,99%. Hence, the conclusion of the research shows that there is significant effect in using student worksheet based on SAVI approach in integrated science subject type of connected toward the achievement of science competence of students grade VIII SMPN 12 Padang